2021
DOI: 10.3390/en14041046
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Strategies to Reduce Exhaust Emissions from Passenger Cars in Rzeszow City—Poland. A Preliminary Assessment of the Results Produced by the Increase of E-Fleet

Abstract: Urban agglomerations close to road infrastructure are particularly exposed to harmful exhaust emissions from motor vehicles and this problem is exacerbated at road intersections. Roundabouts are one of the most popular intersection designs in recent years, making traffic flow smoother and safer, but especially at peak times they are subject to numerous stop-and-go operations by vehicles, which increase the dispersion of emissions with high particulate matter rates. The study focused on a specific area of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…According to the World Health Organization (WHO), more than seven million deaths in 2012 are attributed to ambient air pollution globally [5]. Several studies showed that the adoption of electro-mobility (e-mobility) in transportation can reduce harmful exhaust components and mitigate climate change impact [6]. E-mobility is emerging rapidly as a green and sustainable technology in transportation systems.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), more than seven million deaths in 2012 are attributed to ambient air pollution globally [5]. Several studies showed that the adoption of electro-mobility (e-mobility) in transportation can reduce harmful exhaust components and mitigate climate change impact [6]. E-mobility is emerging rapidly as a green and sustainable technology in transportation systems.…”
Section: Introductionmentioning
confidence: 99%
“…In Dublin, Republic of Ireland, research shows that people prefer self-driving vehicles with clean fuel, and urban transport policies can leverage people's attitudes to promote sustainable urban transport [8]. A study in a specific area of Rzeszow, Poland, shows that converting 25% of existing vehicles into electric vehicles can reduce PM 10 emissions by about 30% [9]. In addition, with the increase in the proportion of electric vehicles, it is considerable to optimize the location planning and design of electric vehicle charging stations (EVCS S ).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is given to air pollution by heavy metals and particulate matter (PM) in areas of high exposure and smog [4][5][6][7][8]. The main causes of poor air quality in Poland include: quality of heating systems used in households [8][9][10][11] and emissions generated by vehicular traffic [8,10,11].…”
Section: Introductionmentioning
confidence: 99%